Optimalisasi Kinerja Pegawai dalam Mewujudkan Pelayanan Prima Dinas Perpustakaan dan Arsip Daerah Provinsi Jambi - Ritonga, Husein; Bafadhal, Husin; Kusnadi, Dedek; Yusuf, Umar; Febriansyah, Noval Ahyar (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2024)
The Jambi Province Regional Library and Archives Service is one of the government agencies that plays a role in providing services in the form of information to the As a public service, the Jambi Province regional library and archives service must be able to provide excellent service, which can be interpreted as the best service. However, the implementation of excellent service strategies is sometimes hampered by the quality of human resources (HR), which is not just inadequate competence but also the attitudes and behavior of HR employees who will be the front line in providing services to the community. This is why Community Service (PkM) activities are carried out so that employee human resources can be optimal in providing excellent service. The methods used in this PkM activity are socialization, tutorials, and discussions. This PkM activity provides direction to employees at the Jambi Province Regional Library and Archives Service. This activity concluded that Community Service Activities (PkM) ran smoothly and well. Implementation of PkM activities has no obstacles starting from observation, activity licensing, to implementation of socialization activities. PkM activities are also supported by the Jambi Province Regional Library and Archives Service and assisted by very proactive PPL students.